Process Evaluation of Three Residential Substance Abuse Treatment (RSAT) Programs in Ohio, 1998-1999 - Latessa, Edward J. ([Verlag nicht ermittelbar], 2003)
This study was a process evaluation of the three residential substance abuse treatment programs in the state of Ohio. These programs include MonDay Community Correctional Institution (MonDay), Mohican Youth Center, and Noble Choices. MonDay is a locally operated, community-based correctional facility for felony offenders to which male and female offenders are sentenced in lieu of prison for a period not to exceed six months. MonDay's RSAT program began in October 1997, and a Therapeutic Community (TC) was fully implemented by January 1, 1998. Offenders identified as needing long-term residential treatment were assigned to MonDay's RSAT for six months. Mohican Youth Center (MYC) is an institutional-based TC and is operated by the Ohio Department of Youth Services. Youth convicted of felonies and assessed as needing long-term residential substance abuse treatment are sent to MYC for the last six months of their sentence. Noble Choices is a TC for adult males within the Noble Correctional Institution, a medium security prison operated by the Ohio Department of Rehabilitation and Corrections. The specific research questions addressed in this study were: (1) What is the profile of offenders being served by the Ohio RSAT programs? (2) What is the nature of the services being delivered by the Ohio RSAT programs? (3) What are the intermediate outcomes of Ohio RSAT programs? (4) How are offenders performing under post-release supervision in terms of relapse and recidivism? and (5) What factors are associated with successful program completion and post-release recidivism and relapse? A one-group post-test design was used to conduct this process evaluation. Each program was studied as a separate entity. The study period for each program began at the date of first admission, which was January 1, 1998, for MonDay, March 3, 1998, for MYC, and October 18, 1998, for Noble Choices. The study period ended on March 31, 1999, for MYC and Noble Choices and on April 30, 1999, for MonDay. The sample consists of 466 individuals, including 90 from MonDay, 343 from MYC, and 33 from Noble Choices. Staff at each of the three sites collected intake, treatment, and termination data on their respective program clients using standardized forms developed by the University of Cincinnati. The intake form was used to collect basic demographic information on each offender along with information on past substance abuse, prior treatment experiences, and criminal history. The termination form collected data on type of termination (successful or unsuccessful) and criminal justice placement and residency upon termination. Each site also provided agency-specific assessment information on each offender. Offenders at MonDay were given the Level of Services Inventory (LSI), which measures the risk of recidivism, and the Adult Substance Use Survey (ASUS), which measures the severity of substance abuse problems. Offenders at MYC were administered the Juvenile Automated Substance Abuse Evaluation (JASAE), which measures the severity of substance abuse problems, and the Youthful Offender Level of Services Inventory (YO-LSI). Offenders at Noble Choices were given the Prison Inmate Inventory (PII), which measures several risk factors. In addition, offenders at MonDay and MYC were given the Personal Drug Use Questionnaire (PDUQ), which measures motivation for treatment at intake and 90 days after intake, and offenders at MonDay also completed the PDUQ upon termination. Offenders at MonDay were also administered a Client Self-Rating Form, which measures levels of social and psychological functioning, at intake, 90 days after intake, and termination. Follow-up forms were sent to probation and parole officers to collect information on MYC and MonDay offenders' treatment and supervision activities during the period of supervision after release from the program. Follow-up data were collected on terminated cases from the date of release until August 30, 1999. Part 1, MonDay Data, consists of data from the LSI, ASUS, and intake, termination, and follow-up forms for offenders at MonDay. The LSI scores provided are: criminal history, employment, financial, family, accommodation, leisure and recreation, companion, alcohol and drug, emotions, attitude/orientation, and total. The ASUS variable measures severity of substance abuse problems and distinguishes between scores of 74 or less and 75 or higher. The intake form provides demographic variables, employment status prior to arrest, variables related to the current offense, date screened for RSAT, date placed in RSAT, criminal history, and substance use history. The discharge form provides variables on date of discharge, type of discharge, living arrangements upon discharge, whether continued drug/alcohol treatment was arranged for client, and criminal justice placement. The follow-up form provides variables on substance abuse treatment after release, other services received after release, employment status, reporting status, drug and alcohol tests after release, whether the offender was arrested after release and for what offense, whether a conviction resulted, and the offender's probation status. Several derived variables are also supplied in Part 1. Part 2, MonDay Client Self Rating Scales Data, includes the offender's date of placement, date of birth, the three dates on which the questionnaire was administered, whether inconsistencies appeared in answers to the questionnaires, and several scales derived from offenders' answers. These scales, which are provided for each of the three occasions the questionnaire was administered, include measures of anxiety, depression, self-esteem, decision-making, risk-taking, hostility, self-efficacy, and antisocial attitudes. Several derived variables are also included. Part 3, MonDay Personal Drug Use Data, consists of variables from MonDay's PDUQ. Scales and answers to the 20 items on the PDUQ questionnaire are provided for all three administrations of the questionnaire. In Part 4, Mohican Data, variables from the MYC intake, termination, and follow-up forms are identical to those from the MonDay forms except for additional intake variables on whether the youth was in school prior to arrest, whether the youth experienced certain school problems, where the youth was living prior to arrest, and whether the youth had a record of running away from home. Variables provide the JASAE summary score, date of YO-LSI administration, and YO-LSI scores in the categories of criminal history, family, education, peer, substance abuse, leisure and recreation, personality and behavior, attitudes/orientation, and total. For each YO-LSI score category an additional variable is provided that indicates whether the score was low, moderate, or high. Several derived variables are also provided. Part 5, Mohican Personal Drug Use Data, consists of scale variables calculated from responses to the MYC PDUQ for both administrations of the questionnaire. These scales are precontemplation, contemplation, determination, action, and maintenance. Part 6, Noble Data, consists of variables from Noble Choices intake, termination, and PII questionnaires. Variables from the intake and termination forms are identical to those taken from the MonDay intake and termination forms. Variables from the PII include scale variables that measure truthfulness, adjustment, judgment, alcohol, drug, antisocial attitudes, violence, distress, self-esteem, and stress. For each of these scales an additional variable is provided that indicates whether scores were low, medium, high, or maximum. Several derived variables are also provided.